Artificial intelligence and Chinese university teachers’ work performance: a synergistic or adversarial relationship - Cai, Xinyi; Wen, Wenhua (Frontiers in Psychology, 2025)
IntroductionWith the widespread adoption of AI by Chinese university teachers in their work processes, an increasing number of complexes work this study aims to examine are being handled by AI. Under these circumstances, as traditional knowledge workers, Chinese university teachers may develop concerns about their career prospects, leading to negative work attitudes and pessimism, which could ultimately affect their work performance.MethodsBased on the knowledge worker’s perspective of relationship between leader and subordinates and through a self-administered survey, valid questionnaires were collected from 423 Chinese university teachers working in 64 Chinese universities, and partial least squares structural equation modeling (PLS-SEM) was employed for data analysis.ResultsIn the result, the study reveals a negative correlation between Chinese university teachers’ AI awareness and LMX, as well as a positive association between servant leadership and LMX. Furthermore, it demonstrates that Chinese university teachers’ LMX is negatively related to turnover intention, which in turn shows a negative relationship with work performance.DiscussionAgainst the background of widespread AI adoption in China, this research provides both theoretical implications and practical suggestions for managing, motivating, and inspiring Chinese university teachers to enhance their work performance and thereby improve organizational performance.